Influence of ihsān (benevolence) on sustaining industrial relations practices at Islamic universities in southeast Asia - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi; Ismail, Yusof; Firmansah, Yayan (Global Academic Excellence, 2024)
Ihsān (benevolence) is frequently overlooked in industrial relations. Conventional methods of industrial relations emphasise compliance with legal and organisational mandates via a tripartite framework. Conversely, ihsān underscores the cultivation of a peaceful and ethical connection between employers and employees. This study explores the influence of ihsān on maintaining industrial connections among employees of Islamic universities in Southeast Asia. The study employed focused group discussions (FGDs) with five faculty members from Islamic universities. Participants contended that ihsān, manifested as trust, mutual cooperation, and a spirit of generosity, possesses superior worth. The participants recounted experiences from Islamic universities that have implemented ihsān for nearly a century, illustrating the viability of these institutions in fostering a harmonious and humane work environment. Participants also advocated for ihsān-driven industrial relations. Thus, this study contributes in terms of ihsān in sustaining harmonious industrial relations practices. However, the study is confined to a limited number of Islamic universities in Southeast Asia. Future research should encompass a more extensive sample of Islamic universities around the region to yield comprehensive findings.